2020
DOI: 10.31234/osf.io/dyxqn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Could Attitudes Toward COVID-19 in Spain Render Men More Vulnerable Than Women?

Abstract: The COVID-1 pandemic affects the whole world. Spain is 3rd in the world and 2nd in Europe with largest number of diagnosed cases. Spanish citizens’ attitudes are important in controlling the pandemic. This research assessed key attitudes of the Spanish people toward COVID-19. One study (n =64) was conducted in a shopping center in Madrid and another (n= 640) online. The results of both studies suggest that women in Spain have a ‘more responsible’ attitude toward the COVID-19 than men. Young adults (18-25 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 17 publications
8
23
0
Order By: Relevance
“…Younger adults, males and those who were unemployed had a lower level of knowledge about COVID-19 in our study population. These trends are similar to studies conducted in China and Spain, where younger adults, males, never-married, less educated, and unemployed perceived the pandemic as less threatening, and scored lower on knowledge, personal concern and compliance with safety measures (23,24).…”
Section: Discussionsupporting
confidence: 84%
“…Younger adults, males and those who were unemployed had a lower level of knowledge about COVID-19 in our study population. These trends are similar to studies conducted in China and Spain, where younger adults, males, never-married, less educated, and unemployed perceived the pandemic as less threatening, and scored lower on knowledge, personal concern and compliance with safety measures (23,24).…”
Section: Discussionsupporting
confidence: 84%
“…Due to the COVID-19 crisis and the limitation of free movement, an intentional opinion-type sampling type was used. The call to participate in the study was made through a link sent by the federations of the different sports ( De La Vega et al, 2020 ). The questionnaire was sent to 338 athletes: 230 Olympic athletes, answering 136 (59%), and 108 Paralympic athletes, answering 39 (36%).…”
Section: Methodsmentioning
confidence: 99%
“…Previous neuropsychological studies have shown the benefits of chess practice in executive functions, facilitating the adaptation to complex or not routine situations (Grau-Perez and Moreira, 2017;Ramos et al, 2018). Therefore, chess players showed an excellent ability for planning, selfcontrolling, coping, or problem-solving (Cuéllar and Díaz, 2009;Aciego et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…COVID-19 confinement produces negative psychological effects, including post-traumatic stress, confusion, or anger ( Brooks et al, 2020 ). In this context, the confinement is the highest rated preventive measure of the Spanish population ( de la Vega et al, 2020 ). During the confinement, most individuals are exposed to an unprecedented situation of unknown duration, being exposed to anxiety, fear, depression, or sleep disruption ( Altena et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%